Reformasi Administrasi Publik, Sudah sampai di mana? - Himsar Silaban; Suherman Djaenudin; Ahmad Muksin (Universitas Prof. Dr. Moestopo (Beragama), 2017)
At least, there are four demands in public administration reform. Firstly, institutionalization of government agencies; secondly, quality enhancement of human resources; thirdly, quality enhancement of public services; and fourthly, regional autonomy issues. Related to institutionalization of government agencies, mainly to nonstructural government agencies, the procurement of vice minister position and also the overlapping supervisory duties affected to inefficiencies in human resources, cost, facilities and infrastructures, and so forth. In the context of quality enhancement of human resources, there is a gap between the competency of graduates which are not compatible with the market demands. The problems of quality enhancement of public services are quite the same. Another important issue which is urgent to be solved by the government, regarding to regional autonomy issues, is high-costed local election which can affect to the abuse of authority or the abuse of district head position by the elected candidates.